COVID-19 Fulfilling Workers 'Economic Rights Positive - Rosidi Ruslan (Journal of Morality and Legal Culture, 2020)
This study aims to analyze the fulfillment of workers' rights, which are favorable for Covid. This research is a normative study that uses a statutory approach. The research data used is secondary data with primary, secondary, and tertiary legal materials. The results show that efforts to protect labor rights are carried out through a regulation of the Ministry of Manpower of the Republic of Indonesia, which requires companies to pay full wages to workers with the status of people under surveillance, suspected COVID-19 who must be quarantined, and salaries according to the law for workers/laborers. Who missed work because of COVID-19.